2019
DOI: 10.1021/acsami.8b17709
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Janus Particles: Challenges and Opportunities for the Design of Active Functional Interfaces and Surfaces

Abstract: Janus particles are a unique class of multifunctional patchy particles combining two dissimilar chemical or physical functionalities at their opposite sides. The asymmetry characteristic for Janus particles allows them to self-assemble into sophisticated structures and materials not attainable by their homogeneous counterparts. Significant breakthroughs have recently been made in the synthesis of Janus particles and the understanding of their assembly. Nevertheless, the advancement of their applications is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 220 publications
0
95
0
1
Order By: Relevance
“…During the past 20 years, the research on JPs has prospered (Fig. 1b,c) including manifold synthetic routes for the fabrication of JPs, investigation of their properties, computer simulations as a new perspective to investigate perfect monodisperse Janus particles [21][22][23][24], and their potential for various application fields [25].…”
Section: Janus Particlesmentioning
confidence: 99%
“…During the past 20 years, the research on JPs has prospered (Fig. 1b,c) including manifold synthetic routes for the fabrication of JPs, investigation of their properties, computer simulations as a new perspective to investigate perfect monodisperse Janus particles [21][22][23][24], and their potential for various application fields [25].…”
Section: Janus Particlesmentioning
confidence: 99%
“…Dimer particles with two different chemical compositions, also called Janus particles, have great potential in colloidal surfactant, display, microlaser and drug release [85,86,87,88,89] . Similar to surfactant molecules, Janus dimer particles could also be amphiphilic and have a much stronger anchoring strength at the water/oil interface.…”
Section: Applicationsmentioning
confidence: 99%
“…Dimer particles with two different chemical compositions, also called Janus particles, have great potential in colloidal surfactant, display, microlaser and drug release. [85,86,87,88,89] Similar to surfactant molecules, Janus dimer particles could also be amphiphilic and have a much stronger anchoring strength at the water/oil interface. We successfully prepared amphiphilic dimer particles consisting of a hydrophobic PLA bulb and a hydrophilic shellac-PEG bulb and demonstrated that by engineering the diameter ratio of the dimer particles, i. e. the ratio of the hydrophobic bulb to the hydrophilic bulb, the curvature of the water/oil interface could easily be tuned, thus giving a flexible control over the type of emulsions, as shown in Figure 5a.…”
Section: Applications Of Dimer Particlesmentioning
confidence: 99%
“…11,12 Other uses include nanomotors and nanojets, electronic displays, anti-reective surfaces, etc. [13][14][15][16][17] One remarkable use of Janus nanoparticles is as building blocks for nanoparticle self-assembly, enabling an advance in elds such as molecular colloids or supracrystals. 16,18,19 Therefore, a huge effort has been dedicated to the synthesis of novel Janus nanoparticles with a variety of morphologies and high uniformity, as well as their use in the generation of novel selfassembled suprastructures.…”
Section: Introductionmentioning
confidence: 99%